2016
DOI: 10.1002/ajh.24584
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic events rather than antigen selection pressure may be the main driving forces for relapse in diffuse large B‐cell lymphomas

Abstract: Little is known on the phylogenetic relationship between diagnostic and relapse clones of diffuse large Bcell lymphoma (DLBCL). We applied high throughput sequencing (HTS) of the VDJ locus of Immunoglobulin heavy chain (IGHV) on 14 DLBCL patients with serial samples, including tumor biopsies and/or peripheral blood mononuclear cells (PBMC). Phylogenetic data were consolidated with targeted sequencing and cytogenetics. Phylogeny clearly showed that DLBCL relapse could occur according either an early or a late d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Analysis of longer IGHV gene sequences is required to provide more detailed information on clonal evolution, particularly since binding of IGHV4-34 to self-proteins mostly relies on the FR1 region (38). This is in line with a previous study of paired diagnosis-relapse DLBCL samples, which did not detect signi cant evolution of the antigen selection pressure related to changes in IG sequences, suggesting that lymphomaassociated genetic alterations, but not antigen selective pressure, drive relapse development (41).…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of longer IGHV gene sequences is required to provide more detailed information on clonal evolution, particularly since binding of IGHV4-34 to self-proteins mostly relies on the FR1 region (38). This is in line with a previous study of paired diagnosis-relapse DLBCL samples, which did not detect signi cant evolution of the antigen selection pressure related to changes in IG sequences, suggesting that lymphomaassociated genetic alterations, but not antigen selective pressure, drive relapse development (41).…”
Section: Discussionsupporting
confidence: 91%
“…DLBCL, not otherwise specified (DLBCL, NOS), is classified into two distinct groups, the germinal center B-cell-like (GCB) subtype and non-GCB subtype, characterized by different cells-of-origin (COO) and responses to chemotherapies or targeted therapies [67]. Both subtypes of DLBCL display established features of canonical SHM, while GCB cases exhibit ongoing SHM associated with poorer survival, and non-GCB were considered mutated [48,53,56,68]. High rates of SHM in DLBCL were verified in both the HCDR3 region and the LCDR3 region of BCR, with a worse prognosis in the former case and a better prognosis in the latter case [56].…”
Section: Ig Gene Rearrangement Pattern In Dlbclmentioning
confidence: 99%
“…The hypothesis that, to exert its oncogenic effects, c-Rel would not need additional genetic events is fully in agreement with the fact that the genomic imbalance complexity of DLBCL cases with the c-Rel signature was markedly decreased. It has been shown that, rather than the antigenic pressure, oncogenic events are the main driving forces for relapse in DLBCLs (48). Like in chronic lymphocytic leukemia in which the cytogenetic complexity is associated with resistance to therapies, increased imbalance genomic complexity in non-c-Rel cases is very likely to be related to genetic instability that would favor the selection of a therapy resistant DLBCL subclone.…”
Section: Discussionmentioning
confidence: 99%